Eu(III)-functionalized In-MOF (In(OH)bpydc) as fluorescent probe for highly selectively sensing organic small molecules and anions especially for CHCl3 and MnO4 - Wu, Jing-Xing; Yan, Bing (Journal of colloid and interface science, 2017)
A novel colorimetric luminescent probe has been designed by encapsulating excellent Eu3+ into In-MOF, showing high sensitivity and selectivity of chloroform among several small molecules, as well as MnO4− among anions. [Display omitted] A highly fluorescent metal–organic framework (In-MOF, In(OH)bpydc (bpydc=biphenyl-5,5′-dicarboxylate)) imparting additional luminescent Eu3+ ions has been synthesized for sensing organic molecules and anions, especially chloroform and MnO4−, both of them have a significant spectral response. This Eu3+-incorporated hybrid (In-MOF-Eu) has been fully characterized, which reveals large surface area, great pore size, favorable thermal stability, excellent luminescence as well as good fluorescence stability. On the one hand, the dual-emitting MOF hybrid exhibits a distinctly different response to the chloroform, one of which is almost unchanged, while the other intrinsic broad emission has a remarkable enhancement, leading to an obvious change in color; on the other hand, it also shows a high selectivity for detection of MnO4− because of the largest quenching effect on the luminescent emission, which results in a dark emission. This work represents a new approach for the fabrication of highly selective and sensitive probe for detection of chloroform and MnO4−, as it underlines the opportunity of MOFs with prominent optical properties to explore the existing target substance in the environment.